ANALYTICAL STUDY OF SURVEY RESULTS OF CHEMICAL SAFETY AND SECURITY CURRICULUM IN IRAQI ACADEMIC INSTITUTIONS - Yousif, Emad A; Straut, Christine; Al-Dahhan, Wedad; Al-Lami, Hadi; Hussein, Falah (UNESA Journal of Chemical Education, 2023)
The survey presents a general view of the reality of chemical security and safety in educational institutions in Iraq, in which about 301 university staff from 14 Iraqi universities includes a doctorate, master's and bachelor's degree with a postgraduate student presented their opinions regarding the survey sections. This included basic information related to security and safety curricula and their teaching to students of primary and higher studies in Iraqi universities and ways of communication between universities to improve the reality of teaching and training. These institutions possess a culture of safety and optimal training methods for trainers and students. The opinions of the residents varied, which indicates the disparity of university institutions in terms of performance and infrastructure to improve the reality of security and safety in their institutions. We suggest that the Ministry of Higher Education’s decision-makers take the results of the survey into account to develop future plans and improve the reality of security and safety. Furthermore, it is required to address the negatives and enable universities to communicate with each other to exchange experiences. It is important to take into account the adoption of the principle of transparency in the dissemination of data that would enhance aspects of education and knowledge in educational institutions.